KOMODITI SOSIAL DALAM INDUSTRI MEDIA MASSA - Wangi, Maya Sekar (Universitas Slamet Riyadi, 2007)
ABSTRACT Economic growth has brought effect directly in media structure, so that claim media sector specialization appearance. Requirement of growth of finance growth and up to date business and economics information which can now be seen from special newspaper lift about economic issues, commerce issue and business and housing. Indonesia as state which amount is the biggest population become strategic farm to media do market expansion especially peep out new media industries. Itâ€™s meaning open opportunity to capital owner group to inculcate its capital at information sector. Entertainment and amusement information becomes program having value sell to media, good of electronic media and also media print. Audience and advertisement Â to become market to media industry. Keywords: industrial, mass media, information